Bootstrapping your business start and grow a successful company with almost no money - Gianforte, Greg (BookSurge Publishing, 2007)
The new rules of entrepreneurship from one of the top IPOs of 2004, this book is written for the 8 million entrepreneurs who don't have access to outside capital--or don't want the strings that come attached to it.
Keywords: New business enterprises